ANALISIS PENGGUNAAN MEDIA SOSIAL SEBAGAI MEDIA PEMBELAJARAN MAHASISWA FISIP UHAMKA - Chintya Aidelia Rahma Setia; Deasy Wahyu Hidayati (Universitas Tribhuwana Tunggadewi, 2022)
This study aims to examine YouTube and TikTok social media as learning media for FISIP UHAMKA students. As in this digital era, every student is fluent in using social media, what is not yet is how to use social media as a learning medium. This research was descriptive qualitative using interview and observation methods. The data will be collected and analyzed using triangulation techniques. Based on research that has been done, students often access social media for learning media, supported by data that shows active users of social media are the average age of students. Social media provides a lot of information that is presented in an interesting way, motivates students to think creatively and helps solve problems. The use of social media must be considered and individual awareness is needed, so as not to get addicted to accessing social media that is not used properly and is just a waste of time. It can be said that FISIP UHAMKA students use YouTube and TikTok social media as learning media, this is because students tend to find it difficult to remove their cellphones from their hands, in addition to easy access to YouTube or TikTok social media to help understanding and entertainment and also eliminate boredom.